Grade IV traumatic pancreatic injury with primary duodenum malignant lymphoma following pancreatoduodenectomy: a case report - Ono, Kosuke (Surg Case Rep, 2020)
BACKGROUND: Traumatic pancreatic injury with a main pancreatic duct injury has a high incidence of mortality and requires a prompt and appropriate treatment. However, the best approach, and treatment options, which may be limited, remains controversial especially for the elderly patients. Herein, we present a case of traumatic pancreatic injury in an elderly patient for whom pancreatoduodenectomy was safe and effective. CASE PRESENTATION: An 87-year-old man was diagnosed with a traumatic pancreatic injury with a main pancreatic duct injury. In addition, the horizontal segment of the duodenum was largely eradicated. There were no comorbidities, and his vital signs were stable. A pancreatoduodenectomy was performed. The postoperative course was uneventful, and he was discharged. Pathological examination revealed a primary follicular lymphoma of the duodenum. CONCLUSIONS: This case demonstrated that pancreatoduodenectomy could be performed safely for a severe pancreatic injury in an elderly patient. However, special attention should be paid to select the optimal surgical procedure. Further, this was a rare case, as initially a primary follicular lymphoma of the duodenum was suspected as a duodenal injury coexisting with a traumatic pancreatic injury because of the increased duodenal thickness.